Collaborative Governance in Waste Management at the TPS3R Makmur Jaya KSM, Eka Jaya Subdistrict, Paal Merah District - Amanda, Dia; Muhammad, Hatta Abdi; Elsi, Sutri Destemi (Journal of Governance and Public Affairs, 2024)
Waste is an environmental issue that always remains a major concern, especially in urban areas, including the city of Jambi. Data from the Jambi City Environmental Agency shows that the amount of waste generated per day in Jambi City is 423.45 tons, with the second-highest estimated waste generation located in the Paal Merah District, amounting to 75 tons per day. The highest estimated waste generation is in the Eka Jaya Sub-district, amounting to 22 tons per day. The Jambi City Environmental Agency, PT. PLN UPDK Jambi, and the community in the Eka Jaya Sub-district, Paal Merah District, then collaborated to implement a waste management program at the TPS3R KSM Makmur Jaya. The purpose of this research is to examine how the process of collaborative governance in the waste management program at TPS3R KSM Makmur Jaya, Paal Merah District, is conducted. This research uses a descriptive qualitative research method. Data collection techniques are conducted through interviews, observations, and documentation. The results of this research indicate that collaborative governance in waste management at TPS3R KSM Makmur Jaya is already underway and shows positive achievements in the waste management development process. This can be seen with the presence of processed waste products in the form of compost. However, there are challenges in achieving optimal self-reliance in managing TPS3R. This becomes a barrier to running the program efficiently.